Slow Adaptive Changes in Urease Levels of Tobacco Cells Cultured on Urea and Other Nitrogen Sources - Skokut, Thomas A. (1980)
Tobacco (cv. Xanthi) XD cells cultured for more than a year on urea as the sole source of nitrogen have urease activities about four times higher than cells which have been cultured on nitrate. When cells which had always been grown on nitrate were transferred to urea, the urease activity in these cells remained at a lower level for eight transfers (40 generations), then gradually increased 4-fold during the next seven to 10 transfers. Cells with high urease activity multiplied 19% more rapidly and accumulated less urea than cells with low urease activity. These findings suggest that elevated urease accelerates urea assimilation; therefore, urea limited growth. Clones of cells with low urease activity responded in the same way as uncloned populations when transferred from nitrate to urea, indicating that high urease cells originate from low urease cells, rather than from a preexisting subpopulation of high urease cells. The urease levels in clones of cells from a population with high urease activity were three to seven times the low urease level. The observed dependence of urease activity on generations of growth on urea was matched with a model in which high urease cells originated at mitosis of low urease cells at a frequency of 8 × 10(−5), then multiplied 19% more rapidly than low urease cells. This frequency is about 10(3) greater than that of other biochemical variants previously isolated from XD cells. The high urease activity gradually declined in cells transferred from urea to other nitrogen sources, but rose rapidly when such cells were returned to urea, indicating the existence within the cells of some form of record of their ancestors' growth on urea. The data indicate the existence of a mechanism for generation, at unusually high frequency, of metastable variants with high urease activity. This mechanism, coupled with enrichment for the variants' progeny by virtue of their higher multiplication rate on urea, can account for the observed slow increase in urease activity of the population. It is suggested that the molecular basis of the urease increase may be gene amplification, based on animal cell models. An alternative hypothesis, namely a specific response induced in all cells by urea and manifested as a very slow adaptive increase in urease, has not been ruled out.